(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Measuring the solar radiation received by a plant canopy is necessary to analyze its physiological aspects. A spherical photodiode has been developed for this purpose. However, a horizontally set calibrated solarimeter using a flat type sensor cannot be used for calibration because it must remain unaffected by the cosine law. Therefore, an inexpensive automatic tracking solar disk system has been developed for the calibration of a spherical type solarimeter. A calibrated solarimeter was mounted on the tracking system and was inclined according to the altitude and the declination angle of the location on the day of the experiment. The system calibrated all four spherical solarimeters with high correlation coefficients . Some data exceed the so-called solar constant, which is measured similarly, but outside of the earth atmospheric layer because the device developed this time measured hemispherical solar radiation normal to the sun disk. Similar data were reported even from horizontal measurements.